Spectral broadening for multi-Joule pulse compression in the APOLLON Long Focal Area facility. (10th January 2022) - Bleotu, P.-G.; Wheeler, J.; Papadopoulos, D.; Chabanis, M.; Prudent, J.; Frotin, M.; Martin, L.; Lebas, N.; Freneaux, A.; Beluze, A.; Mathieu, F.; Audebert, P.; et al.
Abstract: Spectral-broadening of the APOLLON PW-class laser pulses using a thin-film compression technique within the long-focal-area interaction chamber of the APOLLON laser facility is reported, demonstrating the delivery of the full energy pulse to the target interaction area. The laser pulse at 7 J passing through large aperture, thin glass wafers is spectrally broadened to a bandwidth that is compatible with a 15-fs pulse, indicating also the possibility to achieve sub-10-fs pulses using 14 J. Placing the post-compressor near the interaction makes for an economical method to produce the shortest pulses by limiting the need for high damage, broadband optics close to the final target rather than throughout the entire laser transport system.